Effectiveness of a protected areas network in the conservation of Tamarindus indica (Leguminosea-Caesalpinioideae) in Benin - Fandohan, Belarmain; Assogbadjo, Achille E; Glèlè Kakaï, Romain L; Sinsin, Brice (African journal of ecology, 2011)
In the absence of effective conservation of its wild relatives, exploitation of a species could lead to genetic depletion. Research on how well do protected areas contribute to the conservation of plant species subject to human exploitation is still limited. The potential niche of Tamarindus indica (tamarind) was evaluated and the contribution of the protected areas network (PAN) of Benin to its conservation was assessed. The maximum entropy approach was used to model the ecological niche of the species, and forest inventories were used to address its population structure. To test its effectiveness, the PAN map was overlapped with the habitat suitability map of the species, and its population structures in protected versus unprotected areas were compared. Tamarindus natural populations were confined to the Sudanian and Sudano-Guinean regions. The species populations in the Sudanian region appeared well represented in protected areas in contrast to those in the Sudano-Guinean region. Results showed a positive effect of protected areas on juvenile density but a weak effect on adult density and current size-class distribution. Protection seemed to be unlikely to ensure the long-term persistence of the species. Cryopreservation, assisted recruitment and artificial enrichment of tamarind stands are recommended to ensure the long-term persistence of the species.